PROSPEK DAN RANTAI PASOK BUNGA MELATI PUTIH (Jasminum sambac) DI KABUPATEN BANJAR PROVINSI KALIMANTAN SELATAN - Fitri Mahyudi; Husinsyah Husinsyah (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2021)
This study aims to determine the ﬂow of products, ﬁnance, information, analyze marketing efﬁciency in the supply chain of jasminum sambac in Banjar Regency and analyze the differences jasminum sambac marketing efﬁciency in the supply chain between Martapura District and Banjar District. This research was conducted in November 2020. The research method used was the survey method. The research was carried out in Martapura District and Banjar District because were the largest centers of jasmine production in Banjar Regency. Determination of farmer respondents was carried out using the Simple Random Sampling method using the Slovin formula, namely 26 respondents in Karang Intan District and 31 respondents in Karang Intan District. Determination of off farm respondents using the Snowball Sampling method, namely 31 farmers, 9 collectors, 5 wholesaler respondents and 12 retail respondents. The analytical method used is descriptive method, marketing efﬁciency analysis method and using a different test independent sample t-test. The supply chain pattern of jasmine flowers in Martapura and Karang Intan Districts is pattern 1, pattern 2 and pattern 3 ,. The largest value of marketing margin and marketing share in Martapura District was Rp 12,462 and 65.87%. The value of the marketing margin and marketing share of Karang Intan District were IDR 13,582 and 69.88%, respectively. Different test results Independent sample t-test on marketing margin, the value of Sig. 2 tailed amounted to 0.246. The results of different test Independent sample t-test on the marketing share obtained the Sig. 2 tailed amounted to 0.221. These results show a number> 0.05, so it can be concluded that there is no significant difference in marketing efficiency between Martapura and Banjar Districts